Effectiveness of Digital Tool Features on Student Learning Outcomes in Nepalese Higher Education Institutions - Sharma, Pratik (Nepalese Journal of Management Science and Research, 2026)
Despite widespread digital tools integration in education, empirical evidence on which features significantly influence student learning outcomes in developing countries remains limited. This study examines the relationship between five digital tool features: Content Quality, Ease of Use, Interactivity, Accessibility, and Peer and Instructor Interaction and learning outcomes among students in Nepal's education sector. Using a quantitative research design grounded in Constructivism and TAM frameworks, data were collected from 362 students across universities and colleges in both urban and rural regions of Nepal through online surveys and field visits. The validated 18-item instrument demonstrated strong internal consistency (Cronbach's Alpha = 0.897). Regression analysis revealed all five features significantly predict learning outcomes, collectively explaining 47.3% of the variance (R² = 0.473). Interactivity emerged as the strongest predictor (β = 0.235), followed by Content Quality (β = 0.207) and Ease of Use (β = 0.187), while Accessibility and Peer and Instructor Interaction also contributed significantly. These findings provide empirical evidence for prioritizing interactive engagement, content quality, and usability in digital learning design. This study enriches the limited quantitative evidence on digital learning in developing countries by highlighting the critical role of interactivity, content quality, and usability in shaping student outcomes within Nepalese higher education.